Study of root characters, leaf yield and yield components of mulberry under high and low soil moisture (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
Root characters, leaf yield and yield components of five mulberry varieties inrelation to soil moisture i.e. well-watered, water- stress and water logging wasstudied in pot condition. Lower root length with higher dry weight were observedin the well-watered plants, on the other hand, shorter root length with lower dryweight was in the waterlogged plants compared to the water-stressed plants. Wellwatered plants had the highest, water-stressed plants had the lowest andwaterlogged plants had the intermediate values for plant height and fresh stemweight. All the leaves of the waterlogged plants were shed at 90 days afterplanting. The water-stressed plants had higher shoot-root ratio followed by thewell-water and waterlogged plants.